Perancangan Alat Pendeteksi Kandungan Alkohol dalam Minuman Berbasis Mikrokontroler - Azwardi Azwardi; Ikhtison Mekongga (JURNAL INTEGRASI, 2012)
In the world of technology, found the smell detection sensor or gas sensor would be very helpful in the industrial world. Some kind of a drink right now is mostly a mixture of chemicals that are harmful to our bodies. ALKOHOL is one such example. Detector ALKOHOL content in the beverage ALKOHOL utilizing young evaporated. The sensor used is TGS2600, TGS2620, and AF63. Where the sensor is very sensitive to the ALKOHOL. In general, the sensor will change its resistance when exposed to ALKOHOL vapors.